Evaluating Online Programs: Challenges and Strategies - Katherine Adler; Mary-Katherine Smith (Academic Chairpersons Conference Proceedings, 2018)
Evaluation of online programs is an elusive blend of art and science. The science is based on a mix of technological opportunities and sound research techniques. This session explores how online education can be evaluated and how the results of the evaluation can be used to guide the growth of improvement of a program.
Keywords: evaluation; online programs